Assessment of Abandoned Unsanitary Landfills in Rural Areas of Ningbo, China - Guan, Yi-Dong; Du, Ye-Hong; Ji, Hong-Fang; Luo, An-Cheng; Zhao, Bing-Wen (Asian Journal of Chemistry, 2011)
This paper reports the characteristics and the pollution status of the abandoned unsanitary landfill which were widespread in the southeast countryside of China. The results show there were at least 100 unsanitary landfills in Ningbo and the waste accumulated was estimated to be equal to the landfill capacity of one large sanitary landfill that had been running for 40 years with an input of 1,000 tons of waste each day. The organic components and Cd content of the rural waste were high, 69.8 g organic matter (OM) kg-1 DW-1 (dry weight) and 17.6 mg Cd kg-1 DW-1 (dry weight) respectively. nitrogen and chemical oxygen demand (COD) were the primary products in the leachate in the unsanitary landfills and its concentrations of macronutrients were much lower than that from the sanitary landfill. The macronutrients (chemical oxygen demand, nitrogen and phosphorus) were the prevalent contaminant in the surface water around the unsanitary landfills. Compared with the reference values, the total nitrogen, total phosphorus and cadmium contents of the soil surrounding the unsanitary landfills had the trend of accumulation. Geoaccumulation index results show the Cd and Zn contamination of the soil were moderately and unpolluted-moderately polluted, respectively.